2019
DOI: 10.5205/1981-8963.2019.242905
|View full text |Cite
|
Sign up to set email alerts
|

Teses e dissertações acerca da história da enfermagem

Abstract: Objetivo: caracterizar a produção e divulgação científica de teses e dissertações acerca da história da Enfermagem. Método: trata-se de um estudo quantitativo, descritivo e bibliométrico realizado no catálogo de teses e dissertações da Coordenação de Aperfeiçoamento de Pessoal de Nível Superior/CAPES, sendo coletados indicadores de caracterização da produção e divulgação científica das teses e dissertações analisados por estatísticas descritivas. Resultados: encontraram-se 1.289 teses e dissertações e, destas,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
1
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 8 publications
3
1
0
4
Order By: Relevance
“…The Universidade de São Paulo (USP) stood out in the number of works produced; its courses are between grades 6 and 7 in the CAPES assessment, and the institution is considered to be a leadership in the country due to its high standard. Similar results were found in a bibliometric study on the history of nursing, in a research in the CAPES database (45) . The fact that USP is a pioneer in offering postgraduation programs in the field of nursing, with a master's degree program since 1973 and a PhD course since 1989, can explain its high production on varied themes (46) .…”
Section: Discussionsupporting
confidence: 86%
“…The Universidade de São Paulo (USP) stood out in the number of works produced; its courses are between grades 6 and 7 in the CAPES assessment, and the institution is considered to be a leadership in the country due to its high standard. Similar results were found in a bibliometric study on the history of nursing, in a research in the CAPES database (45) . The fact that USP is a pioneer in offering postgraduation programs in the field of nursing, with a master's degree program since 1973 and a PhD course since 1989, can explain its high production on varied themes (46) .…”
Section: Discussionsupporting
confidence: 86%
“…Regarding the difficulties encountered in the preparation of the investigation, the lack of information in the abstracts of the studies, such as clarity in the definition of the methodology and explanation of the theoretical framework used, is highlighted. These difficulties were also found in other bibliometric studies (17,35) .…”
Section: Discussionsupporting
confidence: 80%
“…In the case of Graduate studies, as well as the findings of other studies in which the Brazilian academic production was studied (17,25) this study also identified more academic production resulting from Master's dissertations than from Doctoral theses. This data may be related to the fact that the production time of a dissertation is shorter when compared to a thesis (17) which speeds up its publication, in addition to the Master's degree being a prerequisite for the Doctorate. It is noteworthy that theses and dissertations with theoretical nursing references in this period represented only 0.5% of the total production in the country, corroborating similar data found in another investigation (14) .…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Levando em consideração que a enfermagem está inserida no campo de trabalho e nas lutas para consolidação do Sistema Único de Saúde (SUS), desde sua formulação até a consolidação, deve-se destacar que o conhecimento acerca da HSPB, é importante para contribuir com a solidificação da memória da profissão, pois fortalece a identidade profissional e permite a fundamentação da história dos serviços de saúde 6,7 .…”
unclassified